Timescales for exploratory tactical behaviour in football small-sided games - Ric, A.; Hristovski, R.; Gonçalves, B.; Torres, L.; Sampaio, J.; Torrents, C. (Journal of Sports Sciences, 2016)
The aim of this study was to identify the dynamics of tactical behaviour emerging on different timescales in football small-sided games and to quantify short- and long-term exploratory behaviour according to the number of opponents. Two teams of four professional male footballers played small-sided games against two different teams with a variable number of opponents (3, 5 and 7). Data were collected using a combination of systematic observation and a non-differential global positioning system (15 Hz). The temporal diversity and structural flexibility of the players were determined by calculating the dynamic overlap order parameter q, entropy and trapping strength. Analysis of the exploratory dynamics revealed two different timescales, forming a different metastable landscape of action for each constraint. Fast dynamics lasted on average a few seconds and consisted of changes in tactical patterns. The long timescale corresponded to the shared tasks of offence and defence lasting tens of seconds. The players` tactical diversity decreased with an increasing number of opponents, especially in defence. Manipulating numerical imbalance is likely to promote changes in the diversity, unpredictability and flexibility of tactical solutions. The fact that the temporally nested structure of constraints shaped the emergence of tactical behaviour provides a new rationale for practice task design. The manipulation of numerical imbalance on the timescale of a few tens of seconds, on which the exploratory behaviour of players saturates, may help coaches to optimise the exploratory efficiency of the small-sided games.